2023
DOI: 10.3390/rs15112737
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Cropland Exposure to Agricultural Drought in the Greater Mekong Subregion

Wenting Ming,
Xian Luo,
Xuan Luo
et al.

Abstract: Accurate and reliable information on the spatiotemporal characteristics of agricultural drought is important in understanding complicated drought processes and their potential impacts. We proposed an integrated approach for detecting agricultural droughts and their cropland exposure using remote sensing data over the Greater Mekong Subregion (GMS) collected from 2001 to 2020. The soil moisture (SM) dataset (0.05°) was first reconstructed based on an ESACCI SM dataset using a random forest (RF) model. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…Vietnam's water use in the dry season has already exceeded its capacity. Considering that the dry season is the peak period for agricultural water use in the Mekong River Basin [25,32], and our research has found that the main areas with high water demand for fisheries and agriculture in the basin in recent years have shown a significant trend of drought, these areas are more likely to be affected and threatened when a meteorological drought occurs in the basin. Therefore, it is recommended that all regions in the basin properly manage the seasonal allocation of water resources to ensure the agricultural production and water resource security of each community and improve their ability to cope with Meteorological drought [50,51].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Vietnam's water use in the dry season has already exceeded its capacity. Considering that the dry season is the peak period for agricultural water use in the Mekong River Basin [25,32], and our research has found that the main areas with high water demand for fisheries and agriculture in the basin in recent years have shown a significant trend of drought, these areas are more likely to be affected and threatened when a meteorological drought occurs in the basin. Therefore, it is recommended that all regions in the basin properly manage the seasonal allocation of water resources to ensure the agricultural production and water resource security of each community and improve their ability to cope with Meteorological drought [50,51].…”
Section: Discussionmentioning
confidence: 80%
“…Figure 1 illustrates the geographic location, water system distribution, elevation, and land use types. The rainy season (May to October) in the LMRB is dominated by the southwest monsoon from the ocean, resulting in a humid and rainy climate [32]. Conversely, during the dry season (November to April of the subsequent year), the basin is influenced by the northeast monsoon from the continent, leading to dry and less rainy conditions [7].…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Raster data are based on image element arrays to represent geographic information [27], and the specific processing steps are: clipping the data in the range of administrative divisions, resampling the data based on the grid scale, defining projections, and converting coordinates based on the multilevel grid system. In addition, geospatial data are interpolated using interpolation techniques such as inverse distance weighted interpolation [28] to fill in missing values to ensure data integrity. Compared with geospatial data, the data structure of text data is relatively simple, and the specific content of data processing is data cleaning and data standardization.…”
Section: Preprocessing Of Heterogeneous Cropland Big Data From Multip...mentioning
confidence: 99%